Poor sleep pattern is associated with metabolic disorder during transition from adolescence to adulthood - Zhang, Dan; Yang, Yajuan; Zhai, Shuang; Qu, Yang; Li, Tingting; Xie, Yang; Tao, Shuman; Zou, Liwei; Tao, Fangbiao; Wu, Xiaoyan (Frontiers in Endocrinology, 2023)
Objective The purpose of this study was to investigate whether sleep pattern is associated with metabolic disorders among young adults. Methods We measured sleep patterns using multiple sleep behaviors in an ongoing prospective cohort among college students (n = 1,151). At baseline, 729 college students provided fasting blood samples and human body morphological measurements for quantification of metabolic parameters. Then, 340 participants continued to take metabolic parameters measurements at a 2-year follow-up. Sleep patterns were defined by chronotype, sleep duration, insomnia, snoring, and daytime sleepiness. Metabolic scores were derived for four metabolic parameters including body mass index (BMI), waist circumference (WC), fasting blood sugar (FBG), and insulin. Multivariate linear regression model was applied to analyze the association between sleep pattern types and metabolic parameters and metabolic scores. Results In the baseline survey, we found that a total of 41 (4.1%) participants had poor sleep patterns. Then, metabolic scores were significantly higher among college students with poor sleep patterns, compared with those who with healthy sleep patterns at baseline (1.00 ± 0.96 vs. 0.78 ± 0.72, p < 0.05) and 2-year follow-up (0.34 ± 0.65 vs. 1.50 ± 1.64, p < 0.05). After covariates were adjusted, poor sleep pattern (β = 0.22, 95% CI: 0.06 2.53, p = 0.001) was associated with elevated metabolic scores at the 2-year follow-up. Conclusions The elevated metabolic burden observed in college students with poor sleep patterns highlights the need to identify and address sleep problems in order to minimize the long-term impact on disease vulnerability.